Molecular simulation of enhanced separation of humid air components using GO–PVA nanocomposite membranes under differential pressures. Issue 27 (16th June 2022) - Liu, Yilin; Su, Jincai; Duan, Fei; Cui, Xin; Yan, Weichao; Jin, Liwen
Abstract : GO nanoparticle embedding notably promotes the water vapor adsorption but inhibits the nitrogen adsorption in the membrane. Abstract : Hydrophilic nanocomposite membranes have significant advantages in the separation of water vapor which is the core process in air dehumidification. This paper focuses on exploring the micro-mechanism of enhanced separation using graphene oxide–polyvinyl alcohol (GO–PVA) nanocomposite membranes. The sorption and diffusion behaviors of water vapor and nitrogen in GO–PVA membranes were investigated using molecular dynamics (MD) and Monte Carlo (MC) methods. The study showed that embedding GO into a PVA matrix results in a higher glass transition temperature and fractional free volume. The latter is believed to enhance the diffusivity of gas molecules in polymeric membranes. The interaction between the polymer chains and GO nanoparticles notably promotes the adsorption capacity of water vapor and inhibits nitrogen adsorption in the membrane. A water vapor permeance of 8844.07 Barrer and a separation factor of 3.53 could be achieved with the GO–PVA-0.5 membrane. The analysis confirmed that GO has the same effect on single gas and binary gas mixtures, i.e., increasing the water vapor permeability and selectivity. The calculated water vapor permeance of binary gas is 83% lower than that of single gas permeation. It is expected that this research could provide fundamentals for the optimization and synthesis of gas separation membranes.